Oenological Properties of an Interspecific Saccharomyces Hybrid - Rainieri, S.; Zambonelli, C.; Tini, V.; Castellari, L.; Giudici, P. (South African Journal of Enology and Viticulture, 2017)
An interspecific hybrid between a thermotolerant Saccharomyces cereviszae strain and a cold-fermenting Saccharomyces uvarum strain was characterised oenologically. This hybrid was shown to possess the parental traits in a useful combination for winemaking. The wines obtained by the hybrid were characterised by a low titratable acidity. This was due to the ability of the hybrid to degrade malic acid with the same intensity as the thermotolerant S. cerevisiae parental strain. The hybrid produced wines with a volatile acidity that was as low as that obtained using the cold-fermenting S. uvarum parental strain; a high glycerol concentration (obtained from both parental strains) and it fermented as vigorously as most of the S. cerevisiae wine strains at temperatures of oenological interest. This hybrid was successfully used for white wine production and helped to reduce excessive concentrations of malic acid. It was also used for red wine production. In this case the high pH values of the fermented must created an ideal situation for the starting of the malo-lactic fermentation and allowed the production of high quality fullbodied wines.